Assessing carbon greenhouse gas emissions from aquaculture in China based on aquaculture system types, species, environmental conditions and management practices - Kam Tang (Agriculture, Ecosystems and Environment, 2022)
Aquaculture is one of the fastest growing food production sectors in China, but many of the small-hold operations are poorly assessed for their climate impact. We analyzed the literature data on CO2 and CH4 fluxes from various aquaculture systems in China. The mean fluxes varied from -382.45 to 551.88 g CO2-C m-2 yr-1 and -0.03 to 565.09 g CH4-C m-2 yr-1. Aquaculture system reclaimed from mudflat had the highest CH4 emission (54.92 ± 21.00 g C m-2 yr-1) but lowest CO2 emission. Shrimp aquaculture and semi-intensive farming tended to yield higher CH4 emission. Small and shallow systems had significantly higher CO2 and CH4 emissions, with chlorophyll a and dissolved oxygen concentrations among the main environmental drivers. Management practice such as drainage, exposure and desilting during the non-farming period significantly decreased CH4 emission. We estimated that aquaculture systems in China emitted 181.66 Tg CO2-eq yr-1, enough to offset ~7% of the national terrestrial carbon sink, with most of the emission concentrated in coastal provinces and along the major rivers in the southeastern quadrant. This study highlights the need to account for carbon greenhouse gas emissions from aquaculture to improve the accuracy of the regional and national carbon budgets.